Eficácia e custo operacional da pulverização com carrapaticida em bovinos leiteiros utilizando variações no tamanho de gota e na pressão de trabalho - Gabriel Resende Souza (2024)
Rhipicephalus microplus is responsible for causing health problems in animals and economic impacts. Control is achieved through acaricide treatments with chemical products. This study aimed to determine the efficacy and the Effective Operational Cost of acaricide treatments, varying droplet size and pressure. Three experiments were conducted on dairy cows using a stationary power sprayer. In each experiment, three groups of ten animals each were submitted to different treatments. In the first experiment, treatments with equal droplet sizes (medium droplet) were compared at different working pressures (50 and 100 psi) and a full cone spray pattern. In the second experiment, different droplet sizes (fine and medium droplets) were compared at the same pressure (100 psi) and a full cone spray pattern. In the third experiment, different droplet sizes (fine and ultra-coarse droplets) were compared at the same working pressure (100 psi) and different spray patterns (full cone and fan/flat). All animals were treated on day D0 with an organophosphate and pyrethroid-based product (50% chlorpyrifos and cypermethrin high-cis 6%). Tick counts were performed on days +7, +14 and +21 to determine efficacy. During the treatment, data on bath time and product consumption were collected to determine the Operational Effective Cost. In experiment 1, treatment efficacy varied for Group 1 from 70.6 to 88.9%, and for Group 2 from 75.2 to 93.7%. Tick counts showed no significant differences between treated groups on days +7 to +21 (p < 0.05). No difference was observed between treated and untreated groups on day 0 (before treatment), as observed in the other experiments. In experiment 2, efficacy varied for Group 1 from 48.7 to 86.2% and for Group 2 from 68 to 94.7%. Tick counts showed no significant differences between treated groups on days +7 to +21 (p < 0.05). No difference was observed between treated and untreated groups on day 0. In experiment 3, efficacy varied for Group 1 from 62.9 to 76.9%, while for Group 2, it varied from 73.4 to 86.5%. Tick counts showed no statistical differences between days 0 and +21 in all groups. In Group 1, counts on days +7 and +21 were statistically like Group 2 and the Control Group (p < 0.05). In Group 2, counts on days +7, +14, and +21 differed significantly from the Control Group (p < 0.05). Effective Operational Cost ranged from R$ 2.39 to R$ 3.10 (0.46 to 0.60 USD) per bath. The results indicate that larger droplets (medium and ultra-coarse) and higher pressure (100 psi), when compared to smaller ones (fine droplets and 50 psi), exhibit a more effective treatment. Additionally, the flow rate, influenced by droplet size and pressure, determines the primary value of the Effective Operational Cost (COE).